1980
DOI: 10.1021/es60162a004
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of lead in urban dusts. A microanalytical approach to lead tracing

Abstract: Scanning electron microscopy associated with energy dispersive X-ray analysis is used to identify the sources of leadcontaining particles in urban dust. The identities of individual particles (automobile exhaust, paint chips) are established on the basis of characteristic particle morphology and chemical composition. Lead source tracing is greatly facilitated by physically separating and preconcentrating lead-containing particles, but quantitation of the contributions of specific sources requires the combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…5). Variability also exists across the street environment, with different levels of contaminants being present in gutter samples from those in street centres and pavements (Linton et al 1980), highlighting the need to understand the appropriate scale for monitoring studies. There have been few studies on the temporal variability in RDS composition.…”
Section: Sources To Docks and Canalsmentioning
confidence: 99%
“…5). Variability also exists across the street environment, with different levels of contaminants being present in gutter samples from those in street centres and pavements (Linton et al 1980), highlighting the need to understand the appropriate scale for monitoring studies. There have been few studies on the temporal variability in RDS composition.…”
Section: Sources To Docks and Canalsmentioning
confidence: 99%
“…Cu has been suggested to originate primarily from wheel hub and brake lining material (Beckwith et al 1986). Pb has been suggested to originate from fuel (Kim et al 1998 andBeckwith et al 1986) having also been found concentrated in magnetic particles (Linton et al 1980) and Zn has been sourced to tire wear by a number of RDS studies (Hopke et al 1980;Ellis and Revitt 1982;Kim et al 1998;Smolders and Degryse 2002). Background soils in Manchester possess mean concentrations within the range of concentrations for RDS at the three sites (Fe=10,252 μg/g, Mn=254 μg/g, Pb=153 μg/g, Zn=164 μg/g, Cu=75 μg/g; n=10, Robertson 2004).…”
Section: Inter-site Variabilitymentioning
confidence: 99%
“…A number of studies have documented the spatial variability of metal concentrations in RDS, on both the scale of the road-surface (Linton et al 1980) and the city scale (Duggan and Williams 1977;Massadeh and Snook 2002;Robertson et al 2003;Charlesworth et al 2003;Carraz et al 2006). Less information is available on the temporal variability of RDS composition.…”
Section: Introductionmentioning
confidence: 99%
“…Any hypothetical explanation of the urban distribtuion of lead must involve at least two sources: 1) Lead-based paint and 2) vehicle lead emissions. Both sources are a part of the lead dust described in a city (Hunt et al, 1991 ;Hunt et al, 1992;Hunt et al, 1993, Linton et al,, 1980. About 13 million metric tons of lead were used in the manufacture of lead-based paint and leaded petrol.…”
Section: Hypothetical Explanation Of the Urban Pattern Of Lead Concenmentioning
confidence: 99%